Psychosocial Risk Management in the Teaching Profession: A Systematic Review - Elisabeth Wischlitzki; Nadja Amler; Julia Hiller; Hans Drexler (Elsevier, 2020)
Teachers are facing various job demands with psychosocial aspects being fundamental due to the nature of the occupation. Although teachers' work is associated with different psychosocial health risks, little is known on how to identify and tackle those.Thus, a systematic literature search as per the PRISMA statement was conducted via MEDLINE (PubMed), PSYNDEX (PubPsych), and ScienceDirect. Two reviewers independently screened 2261 titles and abstracts and 169 full-texts. According to the inclusion criteria established a priori, articles from peer-reviewed journals (English or German) on psychosocial risk management in teachers were incorporated.Despite a comprehensive and sensitive search, only four publications could be identified, outlining a process to implement risk management and different assessment tools. Taken together, data presented in the articles were scarce.Recommendations for process steps and the assessment of psychosocial risks can be derived from the findings. To implement effective psychosocial risk management in the teaching profession, further research is needed, though. Effective and practicable approaches, which are accepted by the target group, should be further developed and investigated. Relevant causes of occupational strain in the teaching profession must be identified and assessed reliably. Low-threshold interventions should be implemented, and the outcome must be evaluated afterward.